BANK SYARIAH : Antara Labelisasi dan Pemberdayaan Ekonomi Masyarakat - Mansur Mansur (LP2M IAI Miftahul Ulum Pamekasan, 2018)
The concept of Syariah Bank empowerment of the community's economy through its products such as: Mudharabah, Musyarakah, Murabahah, Kafala, and others, is a banking service that reflects its concern for improving the economy and welfare of the poor. While the weaknesses in the internal field such as inadequate institutional factors, and external factors, such as the readiness of the community to accept the presence of the Syariah Bank, are welcome in the National banking system, provided they are accompanied by high progression. The labeling of